MARKETPLACES IN UKRAINE IN THE CONDITIONS OF DIGITAL METAMORPHOSES: TRENDS, CHALLENGES AND STRATEGIC GUIDELINES - Касумов, Теймур А. (Journal of Strategic Economic Research, 2025)
In times of digital metamorphoses and prolonged military instability, the Ukrainian marketplace market has become a space of rapid adaptations, revision of business models and displacement of centers of consumer activity. Marketplaces have become important mechanisms for the functioning of the economy in conditions of resource shortage. The goal is to investigate the transformation processes of three leading Ukrainian marketplaces (Rozetka, Prom.ua and Zakaz.ua), identify characteristic trends, key challenges and directions of strategic maneuvering in conditions of digital restructuring and military pressure. The study uses structural-analytical and comparative-historical approaches, content analysis of empirical sources, graphical modeling and generalization of statistical indicators from open data and industry research. The study allowed us to identify a number of characteristic trends and quantitative indicators that outline the current dynamics of Ukrainian marketplaces. In 2023, Rozetka achieved revenue of approximately UAH 45 billion and had over 399 million visits, which provided it with a share of about 45–50% in the online retail structure. The platform expanded its range to 12 million products and attracted over 20 thousand active partners. Prom.ua, despite a different business model, generated over UAH 5 billion in revenue from commissions and services, and the total sales volume within the EVO ecosystem (including Bigl, Shafa, Crafta, etc.) reached tens of billions of UAH. The platform's traffic in January 2023 was 42.3 million, and the number of orders in the first half of the year increased by 38%. Zakaz.ua, although operating in a more limited e-grocery niche, demonstrated resilience: over 1 million orders, a turnover of about UAH 5 billion, and an average check of UAH 2,255. All three marketplaces actively changed their logistics, product policies, and communication practices in response to the challenges of the war. The market as a whole grew: in 2024, the volume of e-commerce in Ukraine reached UAH 239 billion, and the number of online buyers exceeded 11 million. Thus, not only the adaptability of the platforms was confirmed, but also their ability to set the pace for the digital restructuring of the economy. The conclusions confirm that the transformations of marketplaces in Ukraine took place not in the logic of survival, but in the logic of strengthening their role in new economic chains. Under the weight of digital changes and existential challenges, they became the basis for the formation of an autonomous, internally mobile platform for national business.